2016
DOI: 10.1037/abn0000183
|View full text |Cite
|
Sign up to set email alerts
|

External validity of a hierarchical dimensional model of child and adolescent psychopathology: Tests using confirmatory factor analyses and multivariate behavior genetic analyses.

Abstract: Several recent studies of the hierarchical phenotypic structure of psychopathology have identified a General psychopathology factor in addition to the more expected specific Externalizing and Internalizing dimensions in both youth and adult samples and some have found relevant unique external correlates of this General factor. We used data from 1,568 twin pairs (599 MZ & 969 DZ) age 9 to 17 to test hypotheses for the underlying structure of youth psychopathology and the external validity of the higher-order fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
167
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(187 citation statements)
references
References 46 publications
17
167
1
2
Order By: Relevance
“…These studies have shown that a latent shared genetic factor accounts for up to 45% of co-variance across childhood externalizing, internalizing, and phobia symptoms [31,33] and 31% of covariance in childhood neurodevelopmental symptoms [34]. Similar results have been reported for register-based clinical diagnoses, with one study showing that a general genetic factor explained 10-36% of disorder liability across several psychiatric diagnoses [32].…”
Section: Psychiatric Comorbiditymentioning
confidence: 52%
“…These studies have shown that a latent shared genetic factor accounts for up to 45% of co-variance across childhood externalizing, internalizing, and phobia symptoms [31,33] and 31% of covariance in childhood neurodevelopmental symptoms [34]. Similar results have been reported for register-based clinical diagnoses, with one study showing that a general genetic factor explained 10-36% of disorder liability across several psychiatric diagnoses [32].…”
Section: Psychiatric Comorbiditymentioning
confidence: 52%
“…This structure has replicated in multiple youth samples (e.g., Castellanos-Ryan et al, 2016; Martel et al, 2017; Neumann et al, 2016; Snyder, Young, & Hankin, 2017; Tackett et al, 2013; Waldman, Poore, van Hulle, Rathouz, & Lahey, 2016). Converging evidence demonstrates the p factor is moderately heritable (Neumann et al, 2016; Waldman et al, 2016), has strong distress-related psychopathology loadings (Waldman et al, 2016) and is associated with negative emotionality (Castellanos-Ryan et al, 2016; Tackett et al, 2013) and poor executive function (Castellanos-Ryan et al, 2016; Huang-Pollock, Shapiro, Galloway-Long, & Weigard, 2016; Martel et al, 2017). Thus, one way to conceptualize the p factor is as shared (partially genetic) liability for psychopathology, characterized by transdiagnostic distress, potentially through the endophenotype of poorly-regulated emotion and cognition (e.g., Beauchaine & Zisner, 2017).…”
mentioning
confidence: 78%
“…Importantly, this does not mean that internalizing symptoms are unrelated to chronic stress (see Table 2 showing manifest CDI and MASC correlations with stress), but rather that these associations are likely accounted for by common psychopathology (p factor) rather than relating to specific internalizing variance. Depression and many anxiety disorders (e.g., generalized anxiety) are distress disorders, and distress appears to be mostly captured by the p factor (Waldman et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…We used a common pathways model in a recent new set of analyses of Tennessee Twin Study data (Waldman, Poore, Van Hulle, Rathouz, & Lahey, in press). Unlike our previous independent pathways modeling of the Tennessee Twin Study data (Lahey et al, 2011), which only examined genetic and nonshared environmental influences, potentially important shared environmental influences on psychopathology (Burt, 2014) also were analyzed using the common pathways model.…”
Section: Genetic and Environmental Structure Of Psychopathologymentioning
confidence: 99%
“…Figure 3 presents a full quantitative description of the hierarchy of causal influences on these 11 first-order dimensions of psychopathology in children and adolescents as revealed in the common pathways model fitted to Tennessee Twins Study data (Waldman et al, in press). The three panels in Figure 3 illustrate the patterns of sharing of each type of causal influence.…”
Section: Genetic and Environmental Structure Of Psychopathologymentioning
confidence: 99%